The Effectiveness of English Teaching Module at Middle Schools in West Aceh - Erizar Erizar; Mohd Nazri Latiff Azmi (SCAD Independent, 2017)
The purpose of this study is to explore the effectiveness of English Teaching Module at middle schools in West Aceh. The students of middle school studying in Government public school were the population of study. The control group, as well as the experimental group, was of equal size, each has 30 students of 8th class. The significance of the difference between the scores of groups at 0.05 levels was tested by applying t-test. The result of the study showed the difference between the mean scores of the experimental and control group was found to be highly significant. The p- value was found 0. 000 (P< 0.05). The study also proved that the material designed, which was useful for slow as well as of bright students, enabled the students to comprehend difficult concepts, and kept them on the track.